2021
DOI: 10.3390/ijms22147498
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Collagen Deposition in COVID-19 Post Mortem Lung Samples and Computed Tomography Analysis Findings

Abstract: Lung fibrosis has specific computed tomography (CT) findings and represents a common finding in advanced COVID-19 pneumonia whose reversibility has been poorly investigated. The aim of this study was to quantify the extension of collagen deposition and aeration in postmortem cryobiopsies of critically ill COVID-19 patients and to describe the correlations with qualitative and quantitative analyses of lung CT. Postmortem transbronchial cryobiopsy samples were obtained, formalin fixed, paraffin embedded and stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Six months after infection, the ground-glass pattern resolved, but there was persistence or development of changes suggestive of pulmonary fibrosis, such as reticulation with or without a distortion of the lung parenchyma . Another, more recent analysis with 118 infected patients diagnosed with moderate or severe pneumonia by SARS-CoV-2, adopting a stricter definition of fibrotic changes, found fibrotic-like changes in 72% of cases (SOLOMON, 2021) (BALL, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Six months after infection, the ground-glass pattern resolved, but there was persistence or development of changes suggestive of pulmonary fibrosis, such as reticulation with or without a distortion of the lung parenchyma . Another, more recent analysis with 118 infected patients diagnosed with moderate or severe pneumonia by SARS-CoV-2, adopting a stricter definition of fibrotic changes, found fibrotic-like changes in 72% of cases (SOLOMON, 2021) (BALL, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Both COVID-19 and non-COVID-19 ARDS are characterized by severe refractory hypoxemia and high mortality [ 3 , 4 ]. However, despite several pathophysiological similarities existing between COVID-19 and non-COVID-19 ARDS, some substantial differences should be discussed ( Figure 1 and Figure 2 ).…”
Section: Physio-pathological Differences and Similarities Between Cov...mentioning
confidence: 99%
“…Usually, three histopathological phases are described in traditional ARDS: (1) acute early exudative (1–7 days) with intra-alveolar edema, interstitial widening, formation of hyaline membranes, epithelial disruption, and alveolar distortion; (2) subacute proliferative phase (1–3 weeks) with myofibroblast proliferation and hyperplasia of the epithelial lining; and (3) late fibrotic phase (>3 weeks) characterized by collagen deposition, progressive obliteration of alveolar spaces, and interstitial fibrosis [ 4 ]. Associated thrombi can result as expression of an altered coagulation cascade, which is common in COVID-19 [ 3 ] ( Table 1 ).…”
Section: The Pathophysiology Of Severe Pneumonia/ards Due To Covid-19...mentioning
confidence: 99%
“…Severe COVID-19 pneumonia often requires invasive mechanical ventilation and appears to be a specific phenotype of ARDS (ARDSp), with a distinct histological pattern compared with ARDSexp. Autopsy studies on COVID-19 have reported diffuse alveolar damage, alveolar flooding with the presence of fibrin and hyaluran [ 41 ], intense remodeling [ 42 ], platelet–fibrin microthrombi [ 43 ], and early fibrotic evolution [ 44 ], with variable deposition of collagen fibers [ 45 ]. Despite several similarities with conventional ARDSp, which is characterized by normal endothelium, COVID-19 pneumonia, despite being a pulmonary ARDS, presents in the early stages with endothelial injury and dysfunction induced by direct viral action and host inflammatory response [ 46 ].…”
Section: Pathophysiology Of Severe Covid-19mentioning
confidence: 99%